The story of volcanoes and earthquakes - Matthews, William Henry (Inc., New York Harvey House, 1969)
Explains volcanic eruptions and landforms, the cause and effect of earthquakes, and how seismology benefits man. Includes a glossary and a bibliogaraphy.
Bibliography: p. 116-117.
1
Keywords: Volcanoes -- Juvenile literature; Earthquakes -- Juvenile literature